Validation of a blended teaching model from the perspective of engineering students in Islamic Azad University during the COVID-19 pandemic - Fatemeh Moradi (Universidade Estadual de Alagoas, 2024)
The statistical population included all undergraduate students of engineering fields of Islamic Azad University, Shahreri branch, in the second semester of 2021-2022; overall, there were 201 male and female engineering 201 students who were randomly selected. The questionnaire was completed online by students after explaining the research objectives and attracting the participants. After collecting data, SPSS 26 and Smart PLS software were used for analysis The results showed that the effective factors of face-to-face teaching were: the role of teacher, content and resources, teaching materials, growth and development, the role of family, learning strategies, evaluation, educational goals fulfillment, instruction space and time. The effective factors of virtual education were as follows:   the role of teacher, content and resources, educational materials, the  role of family, growth and development, information technology, learning strategies, learning time,  educational goals fulfillment, evaluation and learning space. On the other hand, the results showed that face-to-face and virtual teaching confirmed and emphasized the need for blended teaching. In other words, blended teaching